The maps of meaning consciousness theory - Andersen, Scott (Frontiers in Psychology, 2024)
Perhaps simply and rather unadornedly, consciousness is having multiple goals for action and the continuously adjudication of such goals to implement action, referred to as the Maps of Meaning (MoM) Consciousness Theory. The MoM theory triangulates through three parallel corollaries, action (behavior), mechanism (morphology/pathophysiology), and goals (teleology). (1) An organism’s consciousness contains a fluid, nested goals. These goals are intentionality, but intersectionality, embodiment meeting the world. I.e., Darwinian inclusive fitness or randomization then survival of the fittest. (2) These goals form via gradual descent under inclusive fitness, the goals being the abstraction of a ‘match’ between the evolutionary environment and organism. (3) Human consciousness implements the brain efficiency hypothesis, genetics, epigenetics, and experience crystallize efficiencies, not necessitating best or objective but fitness, i.e., perceived efficiency based on one’s adaptive environment. These efficiencies are objectively arbitrary, but determine the operation and level of one’s consciousness, termed extreme thrownness. (4) Since inclusive fitness deems mechanism and action efficient and arises one’s goals, embodiment is necessarily entangled to human consciousness as its the intersection of mechanism or action (both necessitating embodiment) occurring in the world that determines fitness. (5) Perception is the operant process of consciousness and is the consciousness’ de facto goal adjudication process. Goal operationalization is fundamentally efficiency-based via one’s unique neuronal mapping as a byproduct of genetics, epigenetics, and experience. (6) Perception involves information intake and information discrimination, equally underpinned by efficiencies of inclusive fitness via extreme thrownness. Perception isn’t a ‘frame rate,’ but a level of threshold of mechanistic activation (via efficiency) and subsequent goal adjudication. (7) Consciousness and human consciousness is a modular (i.e., a level of richness, where levels of complexity build upon previous ones like building blocks) and dimensionalized (i.e., cognitive abilities become possibilities as emergent phenomena at various modularities, like stratified factors in factor analysis) construct. (8) The meta dimensions of human consciousness include intelligence quotient, personality (five-factor model), richness of perception intake, and richness of perception discrimination, among other potentialities. (9) Future consciousness research should utilize factor analysis to parse modularities and dimensions of human consciousness and animal models.